2014
DOI: 10.1016/j.elecom.2014.06.005
|View full text |Cite
|
Sign up to set email alerts
|

High density heterogenisation of molecular electrocatalysts in a rigid intrinsically microporous polymer host

Abstract: A water-insoluble Polymer with Intrinsic Microporosity (or PIM, here for the particular case of the Tröger Base system PIM-EA-TB, BET area ca. 10 3 m 2 g -1 ) is demonstrated to act as a rigid host environment for highly water-insoluble molecular catalysts, here tetraphenylporphyrinato-iron (FeTPP), surrounded by aqueous solution-filled micropores.A PIM-EA-TB film containing catalyst is deposited onto the electrode and immersed for voltammetry (i) with 4-(3-phenyl-propyl)-pyridine to give an organogel, or (ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…The intrinsic microporosity allows other types of molecules to be embedded and solvent to penetrate. It has recently been shown that the "heterogenisation" of water-insoluble tetraphenylporphyrinato-iron (FeTPP) redox catalysts for oxygen reduction is readily achieved within PIM-EA-TB and at a glassy carbon electrode [23]. The resulting porous PIM-FeTPP film effectively immobilised the molecular catalyst (stopping re-distribution and crystallisation) and allowed the aqueous phase to inter-penetrate into the space between the catalyst molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic microporosity allows other types of molecules to be embedded and solvent to penetrate. It has recently been shown that the "heterogenisation" of water-insoluble tetraphenylporphyrinato-iron (FeTPP) redox catalysts for oxygen reduction is readily achieved within PIM-EA-TB and at a glassy carbon electrode [23]. The resulting porous PIM-FeTPP film effectively immobilised the molecular catalyst (stopping re-distribution and crystallisation) and allowed the aqueous phase to inter-penetrate into the space between the catalyst molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel class of microporous organic materials, polymers with intrinsic microporosity (PIM), has been developed. There are a range of potential applications in gas membrane technology [15,16], in electrolyte media as ionic diode [17], and in electrochemical technology [18,19]. The structurally highly…”
Section: Introductionmentioning
confidence: 99%
“…PIMs [23,24] provide a new generation of highly rigid microporous materials with (i) excellent processability, (ii) highly rigid pore structures in which guest catalyst molecules can be readily embedded, (iii) good access of solvent and substrate to the catalyst through rigid pores and (iv) robustness towards corrosion. In our previous work, the poly-amine structure PIM-EA-TB [25] (synthesised based on a Tröger's base reaction [26][27][28]) has been employed to electrochemically grow palladium lamellae [29], to act as a host for molecular Fe(II)-porphyrinato electrocatalyst [30] and to protect gold nanoparticles [31] and fuel cell catalysts [32]. Recently, we have demonstrated proof of concept for the immobilisation of the molecular electrocatalyst 4-benzoyloxy-TEMPO (or 4B-TEMPO) into a porous PIM-EA-TB host film for the electrocatalytic oxidation of saccharides [33].…”
Section: Introductionmentioning
confidence: 99%